Improving Model Interpretability in Credit Scoring Systems through Counterfactual Explanation Frameworks for Equitable and Transparent Financial Decision Making - Sarah Jenkins (Computational Intelligence Systems, 2026)
The rapid integration of complex machine learning architectures into financial services has fundamentally transformed credit scoring, moving the industry away from traditional linear models toward highly non-linear predictive systems. While these advanced models offer superior predictive accuracy, their inherent "black-box" nature presents significant challenges to institutional transparency, regulatory compliance, and social equity. This paper explores the deployment of counterfactual explanation frameworks as a robust system-level solution to the problem of model interpretability in credit scoring. Unlike traditional feature-importance methods that describe global model behavior, counterfactual explanations provide actionable, instance-based insights by identifying the minimal changes in a borrower’s profile required to alter a credit decision. Through a comprehensive interdisciplinary lens, we analyze the structural trade-offs between predictive performance and interpretability, the technical requirements for deploying counterfactual engines within existing financial infrastructures, and the governance implications for ensuring algorithmic fairness. We emphasize the socio-technical nature of credit systems, arguing that interpretability is not merely a technical feature but a prerequisite for institutional trust and the mitigation of systemic bias. By examining the deployment of these frameworks across diverse deployment environments, this research provides a forward-looking perspective on how financial institutions can balance technological innovation with the ethical mandates of transparent and equitable decision-making. The discussion further delves into the sustainability of interpretable infrastructures and the policy shifts required to standardize counterfactual disclosures in the global credit market.